Suomen teollisuustuotannon uudistuminen tuotantolinjatasolla; The Renewal of Production at the Product Line Level in Finnish Manufacturing - Mika Maliranta; Nelli Valmari (The Research Institute of the Finnish Economy (ETLA), 2017)
– We characterize increases and decreases in plant-product -level output sales in the Finnish manufacturing sector during years 2006 to 2015. We show that during the recession of 2008 to 2009, the intensity of variation in plant-product -level sales diminished, and it took several years until the intensity of variation reached its pre-recession level. However in 2015 the intensity of variation was largest since 2006. We also decompose the changes in the plant-product -level output sales into changes in volume and changes in price.
Keywords: L11; L23; L25; L60; O12; 330; Production; Renewal of product structures; Measurement of prices and quantities; Manufacturing; Diversifikation; Industrie; Finnland